Non-invasive High Frequency Median Nerve Stimulation Effectively Suppresses Olfactory Intensity Perception in Healthy Males - Maharjan, Ashim; Peng, Mei; Cakmak, Yusuf O. (Frontiers in Human Neuroscience, 2019)
Median nerve stimulation (MNS) had been performed in the current research to alleviate symptoms of nausea and vomiting. The observed facilitative effects are thought to be mediated by the vagal pathways, particularly the vagus nerve brainstem nuclei of the dorsal nucleus of vagus and nucleus tractus solitarius. Sense of smell is one of the major sensory modalities for inducing vomiting and nausea as a primary defense against potentially harmful intake of material. This study aimed to test effects of non-invasive, high and low frequency MNS on human olfactory functioning, with supplementary exploration of the orbitofrontal cortex (OFC) using near-infrared spectroscopy (NIRS). Twenty healthy, male, adults performed supra-threshold odor intensity tests (labeled magnitude scale; LMS) for 12 food-related odorant samples before and after receiving high-, low frequency MNS and placebo (no stimulation), while cortical activities in the OFC was monitored by the NIRS. Data of the NIRS and LMS test of separate stimulation parameters were statistically analyzed using mixed-model ANOVA. Only the high frequency MNS showed effects for suppressing the intensity perception of the moderate concentration of Amyl Acetate (p:0.042) and strong concentration of Isovaleric Acid (p:0.004) and 1-Octen-3-ol (p:0.006). These behavioral changes were coupled with significant changes in the NIRS recordings of the left (p:0.000) and right (p:0.003) hemispheric orbitofrontal cortices. This is the first study that applied non-invasive, high frequency MNS to suppress the supra-threshold odor ratings of specific concentrations of odors. The vagal networks are potential relays of MNS to influence OFC. Results from the current article implore further research into non-invasive, high frequency MNS in the investigation of its modulatory effects on olfactory function, given its potential to be used for ameliorating nausea and malnutrition associated with various health conditions.